(untitled) (The Journal of Plant Protection Sciences, 2021)
A Parasitoid database consisting of 62 (sixty two) species records gathered by conducting a systematic survey of parasitoids on insect pests of crops in different localities of Manipur was developed by using MS-Access. The database is for academic purpose and it includes the taxonomic details of the parasitoid, host insect, host plant, morphological characters, geographical distribution, period of activity, parasitoid behavior and its biology etc. Image of the parasitoid species are also provided for helping in easy identification of the species.